Model Pendidikan Nonformal Untuk Pemberdayaan Pemuda: Studi Kasus Pada PKBM "Ngudi Laku" di Desa Karanggebang Jetis Ponorogo - Yahya, Fata Asyrofi; Abadi, Said (Kodifikasia, 2025)
This study aims to describe the management of PKBM "Ngudi Laku," analyze the role of agents of change, and analyze the impact of non-formal education at PKBM "Ngudi Laku" on youth empowerment in Karanggebang Village, Ponorogo Regency. Using a phenomenological approach with a qualitative method, the research involved facilitators, the chairman, members, product users, and parents as well as the community as subjects. Data was collected through interviews, observation, and documentation, and then analyzed interactively using the Miles and Huberman model. The findings indicate that the management of non-formal education at PKBM "Ngudi Laku" includes planning, organizing, program implementation, and monitoring and evaluation. The role of the agent of change is manifested as a catalyst, a problem solver, and a connector. This education has an impact on two levels: individual, with changes in perception, awareness, and knowledge of self-concept; and collective, with an increase in skills, the collective ability to start a business, and wider network access, which ultimately improves youth welfare.